1998
DOI: 10.1136/thx.53.6.483
|View full text |Cite
|
Sign up to set email alerts
|

Effect of endogenous nitric oxide inhibition on airway responsiveness to histamine and adenosine-5'-monophosphate in asthma

Abstract: Background-Nitric oxide (NO) may be bronchoprotective in asthma, possibly due to a direct action on airway smooth muscle or through mast cell stabilisation. To investigate this the eVects of two doses of nebulised N G -nitro-L-arginine methyl ester (L-NAME), a non-selective NO synthase (NOS) inhibitor, on exhaled NO levels and airway responsiveness to histamine, a direct smooth muscle spasmogen, and adenosine-5'-monophosphate (AMP), an indirect spasmogen which activates mast cells, were evaluated in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 25 publications
5
27
0
1
Order By: Relevance
“…Subsequent inhibition of NO with NOS-selective inhibitors increased AR (Figs. 5 and 7), suggesting that NO could be acting as a bronchodilator in the case where IL-10 is absent and consistent with prior studies in humans, in which L-NAME increased AR (29). This interpretation would be consistent with fact that a lack of IL-10 results in increased airway NO production, as observed in the present study.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Subsequent inhibition of NO with NOS-selective inhibitors increased AR (Figs. 5 and 7), suggesting that NO could be acting as a bronchodilator in the case where IL-10 is absent and consistent with prior studies in humans, in which L-NAME increased AR (29). This interpretation would be consistent with fact that a lack of IL-10 results in increased airway NO production, as observed in the present study.…”
Section: Discussionsupporting
confidence: 82%
“…This initial expected difference was verified by our exhaled gas measurement technique and subsequently was shown to be altered with administration of NOS-specific inhibitors L-NAME and L-NIL (Fig. 3), similar to findings reported in humans given L-NAME (29). That the brake on NO production was likely present in the IL-10-sufficient case has been shown previously by Todt et al (30), who reported measurable IL-10 protein (0.65-0.75 ng/ml) in the lungs of naïve C57 mice.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Our demonstration that CAT2 is overexpressed is consistent with reports of the elevated levels of arginine and nitrotyrosine in airway epithelial cells of asthmatic subjects (44,45). Previous studies have shown that pharmacologic inhibition of NOS enhances agonistinduced airway constriction in vitro (46,47) and in vivo (46,48,49). In addition, in a guinea pig model of asthma, a specific deficiency of bronchodilating cNOS-derived NO has been shown to contribute to AHR (47,48,50).…”
Section: Discussionsupporting
confidence: 78%
“…This suggests an effect of high doses of corticosteroids in renewing eNOS activity by suppression of iNOS expression. A significant potentiation of NOS inhibitors has also been found in AHR to AMP and histamine, but not to allergen-induced bronchoconstriction in asthmatics (412,413).…”
Section: B No and Airway Hyperresponsivenessmentioning
confidence: 87%